IMPLEMENTASI PROGRAM GERAKAN LITERASI MADRASAH (GELEM) DALAM PENINGKATKAN BUDAYA MEMBACA DAN MENULIS SISWA DI MTSN 3 JOMBANG - Dewi Mukhasonah; Nur ‘Azah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2022)
This research focused on 3 aspects, they are: first, how Madrasah Literacy Activity(GELEM)program in improving students' reading and writing culture is; second, how implementation of the Madrasah Literacy Activity(GELEM)program in improving students' reading and writing culture is; third, what factors that support and inhibit the Madrasah Literacy Activity (GELEM) program in improving students' reading and writing culture are. This research is descriptive qualitative in the form of case study, in collecting the data, the researcher used techniques of interviews, observation, and documentation. The implementation of the Madrasah Literacy Movement (GELEM) program in improving the reading and writing culture of students at MTsN 3 Jombang includes: habituation activities in the madrasa literacy movement with a program of reading non-lesson books and reading 15 minutes before a break, activities in the madrasa literacy movement with a program of coaching activities literacy, writing books and printing books, learning activities in the madrasa literacy movement by integrating literacy culture in learning planning and cultivating literacy into teaching and learning activities.